Akibat Kealpaan Pemilik Lahan Yang Memasang Aliran Listrik - Laimu, Wa Narti; Titahelu, Juanrico Alfaromona Sumarezs; Latumaerissa, Denny (Faculty of Law, Universitas Pattimura, 2024)
Introduction: In criminal law, willfulness (dolus) is the desire and understanding that an action and its consequences occur, while negligence (culpa) is unintentional where caution is required of everyone, so as not to result in negligence resulting in death.Purposes of the Research: The purpose of this study is to discuss and analyze the consequences of the negligence of the land owner who installed electricity resulting in the death of people.Methods of the Research: By using normative juridical legal research methods (legal research). Type of descriptive analysis research. The problem approach consists of a statute approach, a conceptual approach, and a case approach. Sources of legal materials consist of: a) primary legal materials, namely the book of criminal law (KUHP), b) law number 30 of 2009 concerning electricity. Secondary legal materials, namely: doctrines, legal literature theories, research results and scientific articles. Tertiary legal materials are legal dictionaries, Indonesian language dictionaries, and websites. The collection and analysis of legal materials is to collect data, compile it methodically and then analyze it qualitatively to get clarity about the problems at hand.Results of the Research: The results of this study are that due to the negligence of the land owner who installs electricity which results in the death of people, it can be categorized as a crime, where due to negligence or negligence the perpetrator flows his garden fence with high-voltage electric current and does not return to turn off the electricity in succession. Consecutive for two days, and did not notify the local community so as to result in the death of someone. Criminal liability of perpetrators of criminal acts of negligence resulting in the death of another person is regulated in Indonesian positive law regulated in Article 359 of the Criminal Code (KUHP) which restrictively reads: